Bridges Across the Mediterranean Sea: An Introduction to the Maghreb-Southern Europe Migration System - Abreu, Alexandre (2004)
The current geopolitical importance of the Mediterranean isheightened by the fact that it is both a dividing physical barrier between a developed Europe and a chronically peripheral Africa and one of the main structuring corridors for international migration. This note builds on the assumption that the Maghreb-Southern Europe migratory flows are best analysed in a “migration systems” approach and makes a contribution to the awareness of the history andpresent characteristics of the flows within this particular system. The note is divided into five sections: Section 1 further specifies the object of the note; Section 2 provides a brief historical account of the main periods and events of relevance to the dynamics of this migration system; Section 3 is a quantitative analysis of thestocks and flows of North African immigration to European countries in the recent past; Section 4 looks into these flows in further detail, seeking to identify some of their recent characteristics; finally, Section 5 identifies some foreseeable (economic, institutional, demographic,…) developments that are likely to affect the future dynamics of the system.